The relationship between core competence and perceived professional benefits among oncology specialist nurses: A cross‐sectional study - Zhen Li; Lingmin Wang (Wiley, 2024)
Abstract Aim To investigate the current state and influencing factors of core competence of oncology specialist nurses as well as the relationship between core competence and perceived professional benefits. Design A cross‐sectional correlational survey. Methods This questionnaire survey was conducted with oncology specialist nurses working in a Grade III A (tertiary) Public Cancer Hospital in Jinan, China in March 2021. Based on informed consent, a convenience sampling of 350 nurses participated in the study, with 322 valid questionnaires collected. Using IBM SPSS21.0, the data were analysed to perform descriptive statistics, analysis of variance (ANOVA), multiple stepwise regression analysis and Pearson's correlation analysis. Results The overall average score of nurses' core competence was 224.28 ± 7.95, a medium level and the overall average score of their perceived professional benefits was 132.99 ± 5.05. Nurses' core competence was positively correlated with perceived professional benefits. The differences in professional title, education, working years and perceived professional benefits were statistically significant. Conclusion The findings indicated that nurses' perceived professional benefit is an important factor affecting core competence. Nursing managers who take main responsibility for the quality of care should adopt measures to increase perceived professional benefits, which not only promote nurses' job satisfaction and happiness, but also enhance the development of their core competence and the quality of cancer care as well. Patient or Public Contribution All participants contributed to the conducting of this study by completing self‐reported questionnaires.